Dampak Gaya Kepemimpinan Terhadap Motivasi Kerja Karyawan Pada PT.Asuransi Asoka Mas Surabaya - Devi Mayasari; Widodo Widodo; Harsono Teguh; Bambang Karnain; Sugiharto Sugiharto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research aims to analyze the influence of leadership and financial compensation on performance of employees of PT Asuransi Asoka Mas Surabaya. This research data obtained from the questionnaire and some observations and interviews with relevant parties. Research findings show that leadership variable effect on the motivation of working. Research methods used in this study using multiple linear regression analyst. In testing simultaneously by using the F test showed a real influence among variables with variables bound. In the relationship between this generated koefisiens simultaneous determination (R2) of the existing data show that, the third free variables bound variable that is able to explain the motivation of working, while the value of the correlation (R) shows that the relationship between the free variables in its entirety with the variables are bound is quite strong. Partially motivational variables (X1) the dominant effect against the motivation of working with value t calculate > t table. It can be concluded that the performance of employees on the influence by the leadership style against employee motivation.